THE ROLE OF PHYSICS IN MEDICINE AND MRI (MAGNETIC RESONANCE IMAGING) TECHNOLOGY AND ITS BASICS - Tukhtakhodjaeva , Feruza Shamansurovna; Murodullayev , Mironshox Nodirbek o‘g‘li; Imanova , Laura Nurmaxan qizi (Educational Research in Universal Sciences, 2023)
This article explores the fundamental intersection between physics and medical technology, specifically delving into the essential role of physics in the development and functioning of Magnetic Resonance Imaging (MRI). The intricate relationship between physics principles and medical advancements is dissected, shedding light on how the principles of magnetism, radiofrequency, and resonance form the backbone of MRI technology. The article navigates through the basics of MRI, offering readers a comprehensive understanding of the underlying physical principles that enable precise and non-invasive imaging in the medical field.